Utilizing expired goat milk in soap production: synthesis, characterization, and biological assessment - Zulkifli, Norsakina Zurina; Ali, Rosliza; Yaacob, Yanti; Fadzil, Adibatul Husna; Salleh, Nunshaimah (2024)
This study explored the synthesis of soap using expired goat milk powder and assessed its antibacterial efficacy and moisturizing properties. Two soap variants were created: one with plain expired milk and another with strawberry-flavored expired milk. Cooking oil served as the primary fat, and lye was used for saponification. Despite initial challenges with ingredient ratios and rapid solidification, the experiment successfully produced usable soap, which was solid, bubbled well, and was suitable for everyday use. Antibacterial efficacy was tested using Staphylococcus epidermidis. The spread plate and Kirby-Bauer disk diffusion methods were employed, but the soap demonstrated no inhibitory effect on bacterial growth across multiple trials, indicating that the soap lacked antibacterial properties in its current formulation. Moisturizing effectiveness was evaluated on 26 participants over several weeks, revealing a decline in hand moisture levels, likely due to the absence of essential moisturizing ingredients. Although the soap effectively facilitated saponification, it did not contribute to skin hydration. Overall, while expired goat milk can be effectively used to produce soap, the study identified significant limitations in the soap’s antibacterial and moisturizing capabilities. Future formulations should incorporate stronger antibacterial agents and moisturizing ingredients to improve the soap’s overall performance.